The International Patient's Portfolio and Marketing of Turkish Health Tourism - Altin, Ufuk; Bektas, Gulfer; Antep, Zehra; Irban, Arzu (ELSEVIER SCIENCE BV, 2012)
Health tourism is the name given to the travel of individuals from their residences to other places with the purpose of receiving treatment. Turkey has great potential for medical tourism with its geographical location, climate, thermal resources, natural beauties and qualified medical personnel. Health tourism has developed so rapidly during the last 20 years. In this research, a subgroup of health tourism practices done by the patients undergoing surgery in Turkey is discussed. Within this scope, the economic dimensions and marketing of medical tourism, the place of Turkey in the world market, the advantages and disadvantages of the country and the areas that need improvement

are examined. This research paper is prepared to investigate the necessary medical tourism improvements which can be conducted in both public and private sector in our country.
Keywords: Medical Tourism; Medical Tourism in Turkey; The Economic Dimension of Medical Tourism